Diacerein reduces inflammasome activation and SARS-CoV-2 virus replication: a proof-of-concept translational study - Carmo, Helison R. P.; Castillo, Alejandro Rossel; Bonilha, Isabella; Gomes, Erica I. L.; Barreto, Joaquim; Moura, Filipe A.; Davanzo, Gustavo Gastão; de Brito Monteiro, Lauar; Muraro, Stéfanie Primon; Fabiano de Souza, Gabriela; Morari, Joseane; Galdino, Flávia Elisa; et al. (Frontiers in Pharmacology, 2024)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is linked to high mortality, primarily through an intense inflammatory response. Diacerein has emerged as a potential therapy for COVID-19 due to its potential impact in decreasing the inflammasome activation and coronavirus replication. This study aims to explore diacerein's influence in inhibiting both viral replication and the inflammatory response after SARS-CoV-2 infection. Methods: Human peripheral blood mononuclear cells (PBMCs) were obtained from healthy volunteers and infected in vitro with SARS-CoV-2. Additionally, we carried out a pilot randomized, double-blind, placebo-controlled study with 14 participants allocated to diacerein (n=7) or placebo (n=7) therapies every 12 hours for 10 days. The primary endpoint was change in plasma markers of inflammasome activation (NLRP3, caspase-1, and gasdermin-D). Results: In vitro protocols have shown that rhein, diacerein's primary metabolite, decreased IL-1β secretion caused by SARS-CoV-2 infection in human PBMCs (p<0.05), and suppressed viral replication when administered either before or after the virus incubation (p<0.05). This later effect was, at least partially, attributed to its inhibitory effect on 3-chymotrypsin-like protease (SARS-CoV-2 3CLpro) and papain-like protease in the SARS-CoV-2 (SARS-CoV-2 PLpro) virus and in the phosphorylation of proteins related cytoskeleton network (p<0.05). Diacerein-treated COVID-19 patients presented a smaller area under the curve for NLRP3, caspase-1 and GSDM-D measured on days 2, 5, and 10 after hospitalization compared to those receiving a placebo (p<0.05). Conclusion: The indicated mechanisms of action of diacerein/rhein can reduce viral replication and mitigate the inflammatory response related to SARS-CoV-2. These findings are preliminary and require confirmation in clinical trials.